Animal Models of Tuberculosis Vaccine Research: An Important Component in the Fight against Tuberculosis. (8th January 2020) - Gong, Wenping; Liang, Yan; Wu, Xueqiong
Abstract : Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is one of the top ten infectious diseases worldwide, and is the leading cause of morbidity from a single infectious agent. M. tuberculosis can cause infection in several species of animals in addition to humans as the natural hosts. Although animal models of TB disease cannot completely simulate the occurrence and development of human TB, they play an important role in studying the pathogenesis, immune responses, and pathological changes as well as for vaccine research. This review summarizes the commonly employed animal models, including mouse, guinea pig, rabbit, rat, goat, cattle, and nonhuman primates, and their characteristics as used in TB vaccine research, and provides a basis for selecting appropriate animal models according to specific research needs. Furthermore, some of the newest animal models used for TB vaccine research (such as humanized animal models, zebrafish, Drosophila, and amoeba) are introduced, and their characteristics and research progress are discussed.